2010
DOI: 10.1111/j.1478-3231.2009.02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the risk of acute allograft rejection following human liver transplantation

Abstract: These results suggest that vitamin D may favour immune tolerance towards the liver allograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 33 publications
3
69
1
2
Order By: Relevance
“…Several observational studies indicate associations between vitamin D deficiency and disorders of the immune system, such as multiple sclerosis, 33 type 1 diabetes, 34 rheumatoid arthritis 35 and rejection of solid organ allografts. 36 Some studies have also shown beneficial effects of vitamin D supplementation, most notably in the prevention of type 1 diabetes, 37 and amelioration of symptoms of multiple sclerosis by treatment with high dose vitamin D. 38 However, the relevance of these findings is questioned due to the lack of prospective, randomized trials. Such trials are difficult to carry out in diseases with low incidence and slow onset, such as diabetes type 1.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies indicate associations between vitamin D deficiency and disorders of the immune system, such as multiple sclerosis, 33 type 1 diabetes, 34 rheumatoid arthritis 35 and rejection of solid organ allografts. 36 Some studies have also shown beneficial effects of vitamin D supplementation, most notably in the prevention of type 1 diabetes, 37 and amelioration of symptoms of multiple sclerosis by treatment with high dose vitamin D. 38 However, the relevance of these findings is questioned due to the lack of prospective, randomized trials. Such trials are difficult to carry out in diseases with low incidence and slow onset, such as diabetes type 1.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Our findings appear to be in keeping with results published in renal and liver transplantation, where low vitamin D levels have been associated with an increased risk of rejection of transplanted organs. 29,30 In renal transplant recipients, patients receiving vitamin D supplementation had a significant reduction in acute rejection episodes and graft loss. 31 Conversely, vitamin D deficiency has been associated with an increase in allo-reactive T cells in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our clinical trial of heart transplant recipients treated with calcitriol, we did not observe a reduction in cyclosporine or prednisone dose [14]. In a retrospective study, patients with lower pre-operative 25(OH)D had more frequent moderate to severe rejection episodes in the first 2 months after cardiac transplantation [15]. In a clinical non-experimental setting, patients who were supplemented with cholecalciferol (vitamin D 3 ) had fewer rejection episodes [15].…”
Section: Role Of Vitamin D In Allograft Rejectionmentioning
confidence: 67%
“…In a retrospective study, patients with lower pre-operative 25(OH)D had more frequent moderate to severe rejection episodes in the first 2 months after cardiac transplantation [15]. In a clinical non-experimental setting, patients who were supplemented with cholecalciferol (vitamin D 3 ) had fewer rejection episodes [15]. Further prospective human studies are needed to explore the role of 1,25(OH) 2 D and of parent vitamin D in prevention of graft rejection and infection after transplantation.…”
Section: Role Of Vitamin D In Allograft Rejectionmentioning
confidence: 99%